IMPROVING MECHANICAL PROPERTIES OF API X60/X70 WELDED PIPELINE STEEL (Sciences & Technologie. B, Sciences de l'ingénieur, 2004)
The aim of this study is to improving microstructure and mechanical properties of the weldable gas pipeline steel using laboratory mill. To achieve the required microstructure and mechanical properties of thermo mechanically processed HSLA steels, it is necessary to have an idea about the role of composition and process parameters. The large numbers of parameters obtained during the production process in the plant were systematically changed to optimize the strength and toughness properties. The optimized parameters were used for the production of the API X60/X70 steel. However, the controlled cooling after rolling should result in transformed products that provide excellent combination of strength and toughness. The coiling at an appropriate temperature have the advantage of the precipitation strengthening, giving further rise to the high yield strength and also improvement in toughness of the steel. The coiling temperature is a decisive parameter because it determines the beginning of the formation of fine precipitations. Therefore, four different laboratory cooling systems were used, in this study to simulate the rolling conditions of a real industrial Thermo mechanically controlled process (TMCP), as close as possible and to check the possibilities of improving the mechanical  properties of the welded pipeline steel.